Predicting Different Conceptualizations of System Use: The Competing Roles of Behavioral Intention, Facilitating Conditions, and Behavioral Expectation1 - Venkatesh, Viswanath; Brown, Susan A.; Maruping, Likoebe M.; Bala, Hillol (MIS Quarterly, 2008)
Employees’ underutilization of new information systems undermines organizations’ efforts to gain benefits from such systems. The two main predictors of individual-level system use in prior research—behavioral intention and facilitating conditions—have limitations that we discuss. We introduce behavioral expectation as a predictor that addresses some of the key limitations and provides a better understanding of system use. System use is examined in terms of three key conceptualizations: duration, frequency, and intensity. We develop a model that employs behavioral intention, facilitating conditions, and behavioral expectation as predictors of the three conceptualizations of system use. We argue that each of these three determinants play different roles in predicting each of the three conceptualizations of system use. We test the proposed model in the context of a longitudinal field study of 321 users of a new information system. The model explains 65 percent, 60 percent, and 60 percent of the variance in duration, frequency, and intensity of system use respectively. We offer theoretical and practical implications for our findings.